Damage criterion approach to high‐strength steel RHS truss joints. Issue 3 (15th July 2022) - Mohan, Meera; Wilkinson, Tim
Abstract: This paper describes finite element simulations of the structural deformation and material fracture behaviour of high‐strength steel RHS K gap truss joints. The fundamental scope was to examine whether the joint strength predictions based on the behaviour of lower strength and more ductile steel with a yield stress of 355 MPa or less would hold good for higher strength 450 MPa steel with a lower ductility. The FEA reliability analysis indicates that for failure modes associated with local buckling, yielding and deformation (chord side wall failure, chord face plastification and brace failures due to reduced effective width), the existing approach could, with modifications, be extended to cover higher strength tubes, but for failure modes associated with fracture or ductility or modes liable to brittle failure (tearing in the tension brace and chord punching shear), a strength reduction modifying factor was required. The finite element simulations incorporated a damage mechanics approach to calibrate experimental results in both the fracture and deformation modes of failure. The paper proposes a new formulation for strength and incorporates reduced ductility in high‐grade steel with a modifier function that is not based on yield stress, instead recognizes the reduced ultimate strains, damage parameter for fracture and ultimate stress of the material.